Utilization Black Soldier Fly (Hermetia illucens) Maggot Flour in Feed on the Performance of Superior Native Chickens (KUB) - Nova, Tertia Delia; Montesqrit; Yelti, Rabiatul Hasmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
This study aimed to ascertain the influence of black soldier fly (BSF; Hermetia illucens) maggot flour in rations on the performance of KUB chickens. This study used 60 KUB chickens aged 5 weeks, which were maintained until they were 12 weeks old and were placed in 20 boxes measuring 115 cm × 85 cm × 85 cm, each containing three KUB chickens. This investigation used a randomized block design (RBD) with four groups and five treatments. The treatments used in this study were A (0% BSF maggot meal from 15% fish meal), B (25% BSF maggot meal from 15% fish meal), C (50% BSF maggot meal from 15% fish meal), D (75% BSF maggot meal from 15% fish meal), and E (100% BSF maggot meal from 15% fish meal). The treatment rations were formulated with 17.5% isoproteins and 2800 kcal/kg isoenergy. Feed conversion, body weight gain, dietary intake, and income over feed cost (IOFC) were measured. The results indicated that the addition of BSF maggot meal to KUB chicken rations had no significant effect (P>0.05) on feed consumption and feed conversion but had a significant effect (P<0.05) on body weight gain. In conclusion, providing 25% BSF maggot flour from 15% fish flour in the ration can maintain the appearance of KUB chickens.